A matrix problem with line-sums
Last week, one of my junior gave me a Linear Algebra / Matrix problem, which smell like a combinatorial problem (although until now, I haven't found a combinatorial proof of it).
But I will give a sketch of Linear-Algebra proof on this post.
Notice that the Right-Hand-Side is just the matrix
H(k,\lambda)=\begin{pmatrix} k & \lambda & \cdots & \cdots & \lambda \\ \lambda & k &\cdots & \cdots & \lambda \\ \lambda & \lambda & \ddots & \cdots & \lambda \\ \vdots & \vdots & \ddots &\ddots & \vdots \\ \lambda & \lambda &\cdots & \cdots & k\end{pmatrix}
Let X and Y be a n \times n (0,1)-matrix , where the line-sums of X (resp. Y) is equal to k (resp. k+1). Suppose that \begin{equation} XY=(k-\lambda)I_n + \lambda J\end{equation} where J is the n \times n matrix with all entries equal 1, and I_n is identity matrix. If 1+4(k-\lambda) is not a perfect square prove that n=4\lambda +1 and k=2 \lambda.Here is a combinatorial version of the above
Let A=\{1,2,..,n\} and suppose that we have 2n subsets of A, say X_1, X_2, ..., X_n and Y_1, Y_2, ..., Y_n, where each subsets satisfy:After awhile I found a proof using eigenvalues. But now, I'm actually interested on a combinatorial proof of this one, the condition 1+4(k-\lambda) condition seems to be does not have any trivial combinatorial interpretation.
- |Y_i| = |X_i|+1 = k+1 for all i=1,2,...,n.
- For each x \in A, there are exactly k subsets X_{i_1}, X_{i_2}, ..., X_{i_k} and exactly k+1 subsets Y_{i_1}, Y_{i_2}, ..., Y_{i_{k+1}} which contain x.
If 1+4(k-\lambda) is not a perfect square prove that n=4\lambda +1 and k=2 \lambda.
- For any i=1,2,..,n we have |X_i \cap Y_i| = k and while for any 1 \leq i < j \leq n we have |X_i \cap Y_j| = \lambda.
But I will give a sketch of Linear-Algebra proof on this post.
Notice that the Right-Hand-Side is just the matrix
H(k,\lambda)=\begin{pmatrix} k & \lambda & \cdots & \cdots & \lambda \\ \lambda & k &\cdots & \cdots & \lambda \\ \lambda & \lambda & \ddots & \cdots & \lambda \\ \vdots & \vdots & \ddots &\ddots & \vdots \\ \lambda & \lambda &\cdots & \cdots & k\end{pmatrix}
The i-th diagonal entry of this matrix which is equal to k, is just the dot product between the i-th row of X and i-th column of Y, both according to the problem with total sum k and k+1.
From this we can deduce that the i -th column of Y is just a nearly exact copy of i-th row of X, they only differ in one non-zero entry, let's call these entries speciality .
If we separate these so called specialities into a separated matrix P, we will get
Y = X^T + P
where P contains the separated specialities. Furthermore, P is a permutation matrix, namely there is exactly single 1 on each column and exactly single 1 on each row (since otherwise Y would have a row/column with total sum greater than k+1)
Now, we can make P into an identity matrix by right-multiplying Y with some permutation matrices, recall that the right-multiplication of a matrix with permutation matrix will permute the column of the given matrix, while the left multiplication will permute the row.
So choosing permutation matrices \mathcal{P} = P_1 P_2 \cdots P_m where each P_i is a transposition (i.e obtained by interchanging two columns of identity matrix) we make P \mathcal{P} = I.
This make Y into B = X^T \mathcal{P} + I = (\mathcal{P}^T X)^T + I
Observe that \mathcal{P}^T = P_m^T P_{m-1}^T \cdots P_1^T = P_m P_{m-1} \cdots P_1 , since each transposition is symmetric.
Putting A=(P_m P_{m-1} \cdots P_1 X), we see that A is just a row permuted from X, and so the condition of line-sum equals k is still intact. Furthermore, we also make all diagonal entries of A become zero, since by moving those specialities on Y into diagonal, we also moving the respective zeros related to the speciality into the diagonal of X.
A (A^T + I) = P_m P_{m-1} \cdots P_1 (H(k,\lambda)) P_1 P_2 \cdots P_m
but P_m P_{m-1} \cdots P_1(H(k,\lambda)) P_1 P_2 \cdots P_m = H(k, \lambda), this because if we interchange the i-th column and the j-th column of H(k,\lambda) and then interchange i-th row and j-th row, we will back again to H(k, \lambda).
So we have equation
AA^T+A = H(k,\lambda)
Taking the transpose of both sides we have A^T = A, and so the equation becomes A^2+A = H(k, \lambda), with trace(A)=0 and line-sums of A is all k.
Now being a symmetric matrix, A is (orthogonally) diagonalizable, and we can transform the above equation into
D^2 + D = W
where D is diagonal matrix which consists eigenvalues of A, and diagonal matrix W which consists the eigenvalues of H(k, \lambda).
The eigenvalues of H(k,\lambda) are easy too obtain, indeed, by simple calculation we may check that (1,-1, 0, 0, ... , 0)^T, (0,1,-1, 0, ..., 0)^T, ..., (0,0,0,0..., 1, -1)^T, and (1,1,1,...,1)^T are linearly independent eigenvectors of H(k, \lambda) with eigenvalues \underbrace{k-\lambda, k-\lambda, ..., k-\lambda}_{k \, many} and k+\lambda(n-1), respectively.
The eigenvalues of A, is less trivial, observe that since row sum of A is k, we know that k is an eigenvalue of A with eigenvector (1,1,1,1,...,1)^T.
Let say the (multi)-set of eigenvalue of A is \sigma(A)= \{k, l_1, l_2, ... , l_{n-1}\} (sometime called spectrum of A), so \sigma(D^2+D) = \{k^2+k , l_1^2+l_1, ... , l_{n-1}^2+l_{n-1}\} we must have
\{k^2+k , l_1^2+l_1, ... , l_{n-1}^2+l_{n-1}\} = \{k-\lambda, k-\lambda, ..., k-\lambda , k+(n-1)\lambda\}
Let start with k^2+k, if k^2+k=k-\lambda, we will have k^2=-\lambda, this can't be right since \lambda is non-negative and k is non-zero. So we must have k^2+k = k+(n-1)\lambda, and we have
k^2= (n-1) \lambda
Now then we also have l_i^2+l_i = k-\lambda, thus we get
l_i = \frac{-1+\sqrt{1+4(k-\lambda) }}{2} \qquad \text{or} \qquad l_i= \frac{-1-\sqrt{1+4(k-\lambda) }}{2}
But since 1+4(k-\lambda) is not a square l_i is irrational number. But from trace(A)=0 we also have
k+l_1 + l_2 + ... + l_n = 0
so the sum of these irrational numbers is an integer, thus they must occurs in conjugate pairs. It means that exactly \frac{n-1}{2} of l_i is \frac{-1+\sqrt{1+4(k-\lambda) }}{2} while the other \frac{n-1}{2} is \frac{-1-\sqrt{1+4(k-\lambda) }}{2}.
Now each conjugate pairs summed to -1, so we must have l_1 + l_2 + ... + l_{n-1} = -\frac{(n-1)}{2}. Therefore
k-\frac{n-1}{2}=0 \Rightarrow n=2k+1
Substituting this into k^2=(n-1)\lambda we will get k=2\lambda, furthermore back substitution will yield n=4\lambda +1, and we are done.
Update: I typed a quite-long formally written proof in this pdf file.
Post a Comment: